Sensing properties of different classes of gases based on the nanowire-electrode junction barrier modulation - Singh, Nandan (2012)
The role of contact between semiconducting nanowire and metal electrodes in a single nanowire field effect transistor (NW-FET) is investigated for the sensing of different type of gases. Two different types of In2O3 nanowire devices, namely; Schottky contact device (SCD) and Ohmic contact device (OCD) are evaluated. SCD has shown a superior response to the reducing gas (CO) compared to oxidizing gas (NO), while OCD has shown high sensitivity towards oxidizing gas (NO) compared to the reducing gas (CO) under similar working conditions. The sensing mechanism is dominated by the contact resistance at the metal-semiconductor junction in SCD and the change in nanowire channel conductance dominates in OCD. The Schottky barrier height (SBH) was extracted using low temperature current voltage measurement which provided direct evidence for the notion that the barrier height plays a crucial role in the sensing of different types of gases. The sensing mechanism is illustrated in this work for both devices.